Islamic heritage architecture and art III (WIT Press, 2020)
Islamic architecture has enriched design with a wide variety of structural shapes, including unique arches, vaults and domes which allow for new forms to be developed. The influence that these structural forms have in non-Islamic countries was one of the themes of the 3rd International Conference on Islamic Heritage Architecture and Art.